The effect of diabetes on COVID-19 incidence and mortality: Differences between highly-developed-country and high-migratory-pressure-country populations - Ottone, Marta; Bartolini, Letizia; Bonvicini, Laura; Giorgi Rossi, Paolo; , Reggio Emilia COVID-19 working group; Costantini, Massimo; Grilli, Roberto; Marino, Massimiliano; Formoso, Giulio; Formisano, Debora; Venturi, Ivano; Campari, Cinzia; et al. (Frontiers in Public Health, 2023)
The objective of this study was to compare the effect of diabetes and pathologies potentially related to diabetes on the risk of infection and death from COVID-19 among people from Highly-Developed-Country (HDC), including Italians, and immigrants from the High-Migratory-Pressure-Countries (HMPC). Among the population with diabetes, whose prevalence is known to be higher among immigrants, we compared the effect of body mass index among HDC and HMPC. A population-based cohort study was conducted, using population registries and routinely collected surveillance data. The population was stratified into HDC and HMPC, according to the place of birth; moreover, a focus was set on the South Asiatic population. Analyses restricted to the population with type-2 diabetes were performed. We reported incidence (IRR) and mortality rate ratios (MRR) and hazard ratios (HR) with 95% confidence interval (CI) to estimate the effect of diabetes on SARS-CoV-2 infection and COVID-19 mortality. Overall, IRR of infection and MRR from COVID-19 comparing HMPC with HDC were 0.84 (95%CI 0.82-0.87) and 0.67 (95%CI 0.46-0.99), respectively. The effect of diabetes on the risk of infection and death from COVID-19 was slightly higher in the HMPC than in the HDC (HRs for infection: 1.37 95%CI 1.22-1.53 vs. 1.20 95%CI 1.14-1.25; HRs for mortality: 3.96 95%CI 1.82-8.60 vs. 1.71 95%CI 1.50-1.95, respectively). No substantial difference in the strength of the association was observed between obesity or other comorbidities and SARS-CoV-2 infection. Similarly for COVID-19 mortality, HRs for obesity (HRs: 18.92 95%CI 4.48-79.87 vs. 3.91 95%CI 2.69-5.69) were larger in HMPC than in the HDC, but differences could be due to chance. Among the population with diabetes, the HMPC showed similar incidence (IRR: 0.99 95%CI: 0.88-1.12) and mortality (MRR: 0.89 95%CI: 0.49-1.61) to that of HDC individuals. The effect of obesity on incidence was similar in both HDC and HMPC (HRs: 1.73 95%CI 1.41-2.11 among HDC vs. 1.41 95%CI 0.63-3.17 among HMPC), although the estimates were very imprecise. Despite a higher prevalence of diabetes and a stronger effect of diabetes on Covid-19 mortality in HMPC than in the HDC population, our cohort did not show an overall excess risk of COVID-19 mortality in immigrants.